Process Evaluation for Electrolyzed Sustainable Aviation Fuel (eSAF) (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
Electrolyzed sustainable aviation fuel (eSAF) produced from captured carbon dioxide and renewable hydrogen is a promising pathway to decarbonize aviation, yet it remains electricity intensive and cost sensitive. This study develops a plant-wide Aspen Plus® process model integrating: (i) CO2 capture and conditioning, (ii) alkaline water electrolysis for green H2 generation, and (iii) reverse water gas shift and Fischer Tropsch synthesis (RWGS-FTS) followed by product separation into eSAF and other hydrocarbon products, such as naphtha and renewable diesel. To improve system efficiency, FT tail gas is conditioned via water knock-out and hydrogen recovery prior to conversion in a proton exchange membrane fuel cell (PEMFC) to offset purchased electricity. A base-case eSAF capacity and ±30 % scale scenarios are evaluated to establish consistent mass, energy and carbon balances and to perform techno-economic analysis (TEA). The TEA framework estimates the minimum fuel selling price (MFSP) and quantifies dominant cost drivers of electricity, electrolyzer performance, and CO2 capture energy, complemented by sensitivity analysis to identify the most influential parameters governing eSAF competitiveness.